2014
DOI: 10.1021/jp501756t
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Logic Functions Based on Small Molecular Fluorene Derivatives and Their Application in Cell Imaging

Abstract: Multiple logic functions including dual-input dual-output NOR and AND gates, dual-input dual-output NOT and AND gates, and a three-input NOR gate are fabricated with fluorene-based small molecule/DNA probes (named FSM/DNA probes), which sequences are well-designed. The FSM/DNA probes can be quenched by dsDNA, aptamer-target complex and free dyes (SG I and EB) without the attachment of additional quencher moiety. The quencher-free FSM/DNA probe also presents a way for detection of ATP. In addition, the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Moreover, “ON–OFF” switching of the absorbance of the receptor suggests the reversible nature of the “Writing–Reading–Erasing–Reading” device (Figure S21, Supporting Information). Although the “ON–OFF” state is even clearly observed after five cycles, it should be noted that a gradual decrease in absorbance occurred as a result of the concentration dilution of the system …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, “ON–OFF” switching of the absorbance of the receptor suggests the reversible nature of the “Writing–Reading–Erasing–Reading” device (Figure S21, Supporting Information). Although the “ON–OFF” state is even clearly observed after five cycles, it should be noted that a gradual decrease in absorbance occurred as a result of the concentration dilution of the system …”
Section: Resultsmentioning
confidence: 99%
“…Among several methods (e.g. luminescence, colorimetric and electrochemical), photoluminescence is a broadly used characterization technique for logic devices because of its characteristics such as high sensitivity, simple and fast response 5 10 19 20 21 . We establish the C-dots based fluorescence off-on and on-off sensors which sense the metal ions as well as anions in pH 7.2 HEPES-buffered water solution.…”
mentioning
confidence: 99%
“…We observed that in presence of either Fe 3+ or Fe 2+ /H 2 O 2 (input=1), the fluorescence of 1′ was quenched (output=0). This behaviour is similar to construct a NOT logic gate (Figure S31, Supporting Information) …”
Section: Resultsmentioning
confidence: 78%
“…This behaviour is similar to construct aN OT logic gate (Figure S31,Supporting Information). [39] In addition, the treatment of Fe 3 + -1' system with AA (input = 1) can regenerate the fluorescenceo fthes ystem (output = 1). This leads to the formation of aY ES logic gate ( Figure S32, Supporting Information).…”
Section: Logic Gate Constructionmentioning
confidence: 99%